In Vitro Susceptibility of 57 Isolates of Plasmodium Falciparum to Atovaquone And Lumefantrine in Abidjan - David, Trebissou Jonhson Noel; Sylvain, Beourou; Brice k, Bla; William, Yavo; Joseph, Djaman Allico (The International Journal of Biotechnology, 2013)
To evaluate the in vitro chemosensitivityof Plasmodium falciparum isolates to lumefantrine (LUM) and atovaquone (ATO). The measurement of the in vitro activity of the two antimalaria molecules was conducted according to the microtest optical variant of the WHO. Out of 64 Plasmodium falciparum isolates tested, 57 (89%) gave interpretable results of in vitro culture. It was found that 67% of them were susceptible to LUM against 33% who were resisting. All were sensitive to ATO. The presence of Plasmodium falciparum isolates resistant to LUM could compromise the effectiveness of artemether-lumefantrine recommended in the treatment of uncomplicated malaria in Côte d'Ivoire. While the combination atovaquone / proguanil is a suitable regimen for malaria prophylaxis.